As práticas integrativas complementares em Cuiabá-MT - Damasceno, Adriano Nunes (2023)
Health care has been a longstanding tradition in human societies, and in Brazil, it became a constitutional duty in 1988, establishing citizens’ eights and the state’s obligation through Law 8080/90, which instituted the Unified Health System(SUS) and organized services into three levels of complexity: Primary Care (Low complexity), Secondary Care (medium complexity), and Tertiary Care (high complexity). This research took place at HorPICs with the contribution of the interviewed physician, Otilia Maria Teófilo, a piommer in Integrative and Complementary practices (PICS) in Cuiabá. I conducted participant observation of practices at the Garden and a Basic Health Unit in Cuiabá-MT, with the Integrative and Complementary Health Practices (PICS) and a reference for comprehensive health care in the Bela Vista region on Wednesdays. As this ethnographic study focused on integrative therapies often labeled as “alternative practices”, I selected specific sessions of auriculotherapy and Reiki to understand the interaction between health professionals and SUS users in spaces traditionally associated with allopathic medicine, considering that these practices occurred with the consent of all parties involved. Beyond conventional practice, the description of these health care practices dress parallels with the rituals of traditional communities, a sensitivity well received, particularly by those seeking assistance. The context of the Covid-19 pandemic guided the research to comprehend that PICS were also crucial for individuals grappling with anxiety and distress amid conflicting information, contagion fears, and the imminent loss of loved ones.